The Effect of Using Two Teaching Models of Constructivism on the Motivation Towards Learning Science - Enas S. Abulibdeh; Ghaleb M. Bani Essa; Haytham M. Bani Hani (Sultan Qaboos University, 2016)
This study aimed at investigating the effect of using two teaching models of constructivism on the motivation towards learning science. The sample of the study consisted of 211 male and female students from grade 8. They were distributed into three groups: The first experimental group which was taught by using a Bybee Model and consisted of 71 students, the second group consisted of 70 students and it was taught by adopting Zahorik model, while the third group (the control group) consisted of 71 students and it was taught by adopting the traditional method of teaching. The researchers used a 35- item questionnaire to measure student motivation toward learning science. Findings of the study indicated that there were statistically significant differences on all dimensions of the overall measure of motivation due to the impact of the teaching model, and came to favor the two experimental groups compared to the traditional group. And to favor first group which was taught by Bybee model compared to the group which was taught by Zahorik model. There were also statistically significant differences on the overall measure of motivation, due to the effect of gender; the differences were in favor of females.